2007
DOI: 10.1016/j.ejheart.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous inhibitors of hypertrophy in concentric versus eccentric hypertrophy

Abstract: Left ventricular (LV) hypertrophy (LVH) is an adaptive response to hemodynamic overload, but also contributes to the pathogenesis of heart failure. LVH can be concentric (cLVH) but subsequent dilatation and progression to eccentric hypertrophy (eLVH) may lead to global pump failure. Recently, several endogenous molecular inhibitors of hypertrophy have been identified. Using real-time PCR, we compared the myocardial mRNA expression of these inhibitors in pressure-overload induced cLVH (severe aortic stenosis) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…There are clear differences in gene expression and patterns of signal transduction between concentric and eccentric hypertrophy (33,45,67); however, it is still unclear whether the different phenotypes are due to activation of distinct signaling pathways or differences in temporal and spatial activation of the same signaling proteins. Activation of ERK5 has been implicated in the development of eccentric hypertrophy, since transgenic mice with elevated ERK5 activity developed eccentric cardiac hypertrophy, which rapidly progressed to dilated cardiomyopathy and resulted in premature death (70).…”
Section: Signaling Pathways In Concentric and Eccentric Hypertrophymentioning
confidence: 99%
“…There are clear differences in gene expression and patterns of signal transduction between concentric and eccentric hypertrophy (33,45,67); however, it is still unclear whether the different phenotypes are due to activation of distinct signaling pathways or differences in temporal and spatial activation of the same signaling proteins. Activation of ERK5 has been implicated in the development of eccentric hypertrophy, since transgenic mice with elevated ERK5 activity developed eccentric cardiac hypertrophy, which rapidly progressed to dilated cardiomyopathy and resulted in premature death (70).…”
Section: Signaling Pathways In Concentric and Eccentric Hypertrophymentioning
confidence: 99%
“…Sussman et al (43) showed that FK506 attenuates pressure overload hypertrophy. Another potential candidate is Txnip, an inhibitor of thioredoxin (22 A third potential candidate is S100A9, a member of the S100 family of EF-hand calcium binding proteins, implicated in cell growth mediated through NF-B (16) Another member of the calgranulin family, S100A4, is upregulated in hypertrophy (41).…”
Section: ϫ/ϫmentioning
confidence: 99%
“…Few studies have shown no such association between the pathway of eccentric hypertrophy and activation of fetal marker genes of pathological cardiac hypertrophy. MHC (Myosin heavy chain), which is associated with increased myosin ATPase activity, enhancement of contractility and ventricular function, increased aerobic training and related exercises 39 . Chronically performed aerobic training induces cardiovascular changes; resting bradycardia has been considered to be the main effect of aerobic exercise training adaptation.…”
Section: Aspects and Associated Signaling Of Cardiacmentioning
confidence: 99%